Wybrane potrzeby edukacyjne a sytuacja materialna gospodarstw domowych w Polsce - Grześkowiak, Alicja; Stanimir, Agnieszka (Selected educational needs and financial situation of households in Poland, 2005)
This paper presents the analysis of the degree of satisfaction of some educational needs in Poland. The financial situation of households is the background of the study.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 179-190